Da'wah transformation as a response to community solidarity and government regulations - Mochammad Irfan Achfandhy; Lina Amiliya; Nik Amni Sajidah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - The purpose of the study elaborates on how the da'wah transformations were carried out by the da'i in response to the tension between a sense of solidarity and government regulations related to the Covid-19 Health Protocol.Method - This study uses a descriptive qualitative approach with a case study strategy. Data collection is obtained from participant observation and interviews with da'i and group administrators.Result - The results showed that the actualization of da'wah transformation includes the convergence of da'wah media, collaborative da'wah messages and personal assistance to the congregation after the da'wah. As a result, the research findings show that the response from da'wah activities can be an alternative to minimize social conflict as well as a government stakeholder in campaigning for the Covid-19 Health Protocol.Implication – Recommendations for future research can be made by taking and determining more complex research objects from various different backgrounds. Thus, da'wah science will be increasing widespread and da'wah activities can answer the needs of society in the current era.Originality – This research is a multidiciplinary study between da'wah and culture in response to high community solidarity and government regulations in the covid-19 pandemic era***Tujuan – Tujuan penelitian ini menguraikan tentang bagaimana transformasi dakwah yang dilakukan oleh para da'i dalam menyikapi ketegangan antara rasa solidaritas dan regulasi pemerintah terkait Protokol Kesehatan Covid-19.Metode - Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan strategi studi kasus. Pengumpulan data diperoleh dari observasi partisipan dan wawancara dengan da'i dan pengurus kelompok.Hasil - Hasil penelitian menunjukkan bahwa aktualisasi transformasi dakwah meliputi konvergensi media dakwah, pesan dakwah kolaboratif dan pendampingan pribadi kepada jemaah pasca dakwah. Hasilnya, temuan penelitian menunjukkan bahwa respon dari kegiatan dakwah dapat menjadi salah satu alternatif untuk meminimalisir konflik sosial sekaligus sebagai pemangku kepentingan pemerintah dalam mengkampanyekan Protokol Kesehatan Covid-19.Implikasi – Rekomendasi untuk penelitian selanjutnya dapat dilakukan dengan mengambil dan menentukan objek penelitian yang lebih kompleks dari berbagai latar belakang yang berbeda. Dengan demikian, ilmu dakwah akan semakin meluas dan kegiatan dakwah dapat menjawab kebutuhan masyarakat di era sekarang ini.Orisinalitas – Penelitian ini merupakan kajian multidisiplin antara dakwah dan budaya dalam menyikapi tingginya solidaritas masyarakat dan regulasi pemerintah di era pandemi covid-19.